PENGEMBANGAN APLIKASI PERMAINAN EDUKASI UNTUK ANAK PRASEKOLH MENGGUNAKAN PENDEKATAN CHILD CENTERED DESIGN - Rosa Delima; Nevi Kurnia Arianti; Bramasti Pramudyawardani (Universitas Kristen Duta Wacana, 2016)
This paper discusses the process of developing an education game application using Child Centered Design (CCD) approach. This approach is chosen because the method is suitable for targeted users, preschool students range from 4 to 6 years. The processes of developing the applications consist four stages: the specification of the use of the application, the specification of application requirements, design and application development, and evaluations. Children as the main respondent in this research play an important role in three stages: determining the specifications of the use of the application, the specification of application requirements, and evaluation of applications. Seventy three children are participated in this research. Observation and discussion among the children are used to collect data and information. An observation was conducted to determine the activity and behavior of children, while the discussion method conducted to gather information and opinions of children. In particular, this research involves the interviewer and evaluators who understand the behavior of children and able to communicate with children.